2005
DOI: 10.1093/ecam/neh077
|View full text |Cite
|
Sign up to set email alerts
|

Kampo Medicines for Mite Antigen‐Induced Allergic Dermatitis in NC/Nga Mice

Abstract: We have established an allergic dermatitis model in NC/Nga mice by repeated local exposure of mite antigen for analyzing atopic dermatitis. We examined how four Kampo medicines, Juzen-taiho-to, Hochu-ekki-to, Shofu-san and Oren-gedoku-to, on the dermatitis model to obtain basic information on their usefulness for treating atopic dermatitis. Mite antigen (Dermatophagoides farinaecrude extract) solution at a concentration of 10 mg/ml was painted on the ear of NC/Nga mice after tape stripping. The procedure was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 35 publications
0
65
0
1
Order By: Relevance
“…The development of dermatitis was accompanied by an increase in serum IgE levels and by increased IL-4 and decreased IFN-levels in the splenocytes. According to a report by Gao et al, 22) it was confirmed that continuous application of mite antigens to the auricles of NC/Nga mice once a week for 4 weeks continuously resulted in increased serum IgE levels and in increased IL-4 and decreased IFN-mRNA expression levels in the auricular tissue. We believe that their report corresponds well to the results of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…The development of dermatitis was accompanied by an increase in serum IgE levels and by increased IL-4 and decreased IFN-levels in the splenocytes. According to a report by Gao et al, 22) it was confirmed that continuous application of mite antigens to the auricles of NC/Nga mice once a week for 4 weeks continuously resulted in increased serum IgE levels and in increased IL-4 and decreased IFN-mRNA expression levels in the auricular tissue. We believe that their report corresponds well to the results of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…22) All herbal formulas effectively suppressed dermatitis, and prevented increase of IL-4 mRNA expression and decrease of IFN-g levels. Juzentaihoto and hochuekkito also inhibited IgE hyperproduction.…”
Section: Discussionmentioning
confidence: 96%
“…. 그러나 각종 부작용으로 인해 효과적이 고 안전한 천연물 치료제에 대한 요구가 증가하고 있 으며 24,25) , 이에 따라 치료효과가 높고 부작용이 적은 치료제를 천연물이나 한약에서 찾고자 하는 시도가 끊 임없이 이루어지고 있다 26,27) .…”
Section: Tnf-α 생성 조절에 Nj의 효과를 측정하기 위하여unclassified